Energy dissipation analysis of contact / impact of deformable bodies using numerical modelling - Holiš, Ondřej; Dvořák, Tomáš; Koiš, Matej; Němec, Ivan; Trcala, Miroslav; Vala, Jiří (MDPI, 2026)
The numerical analysis of dissipative energy in dynamic problems involving 1 impact and contact phenomena relies on the physical principles of classical thermodynamics and on the constitutive equations of the material, supplemented by some additional considerations on potential contact interfaces. From the mathematical point of view, we come to a weak form of partial differential equation(s) of evolution with initial, boundary, and interface conditions, whose numerical analysis is required, using the method of discretisation in time and typically the finite element technique. The dissipative energy is an important metric, not merely for quantifying the portion of mechanical work permanently converted to plastic work and thermal energy. Crucially, the localised accumulation of this energy, often expressed as plastic work density, is the primary physical parameter driving microstructural changes, damage initiation, and crack propagation under intense loading. This paper demonstrates how the dissipative energy resulting from material nonlinearities can be evaluated in dynamic problems involving the impact of one body on another and provides a quantitative comparison of numerically calculated dissipated energy using three types of nonlinear constitutive material models, namely the plastic material model with Rankine-Hill criterion, the Mazars damage model, and the Kelvin-Voigt viscoelastic model.
Keywords: building materials; dynamic contact / impact of deformable bodies; dissipative 17 energy; computational modelling